Effect of gestational age on clinical features in necrotizing enterocolitis-associated intestinal perforation - Chen, Minming; Feng, Wei; Hou, Jinping; Die, Xiaohong; Guo, Zhenhua; Wang, Yi (Frontiers in Pediatrics, 2025)
PurposeTo investigate the clinical features of necrotizing enterocolitis-associated intestinal perforation (NEC-IP) in neonates with different gestational ages (GAs). Furthermore, we also want to identify the risk factors of poor prognosis for these patients.MethodsThe retrospective study of patients with NEC-IP was conducted with basic information, comorbidity, intraoperative findings, related treatment, and prognosis. According to the GA, patients were divided into three groups: early (GA: 28–<32 weeks, Group 1), mid-term (GA: 32–<34 weeks, Group 2), and late (GA: 34–<37 weeks, Group 3). The clinical features of the three groups were analyzed, and risk factors for poor prognosis were identified.ResultsOf the 113 cases, the number of cases in Groups 1 to 3 was 36 (31.9%), 44 (38.9%), and 33 (29.2%), respectively; and the overall proportion of poor prognosis was 19.4% (22/113). For basic information, the birth weight of Group 1 was lower than that of Group 2 and Group 3, while the postnatal day at the time of surgery of NEC and the onset age were higher than that of Group 2 (onset age: G1 12.0[7.00;20.5], G2 9.00[4.00;13.0]; postnatal day at the time of surgery: G1 22.0[13.8;27.2], G2 13.0[8.00;21.0]) (P < 0.016). For comorbidity, the incidence of sepsis, coagulopathy, type of (congenital heart disease) CHD, and hypoproteinemia in Group 1 was higher than that in Group 2 (all P < 0.016), and the incidence of respiratory failure, hypoproteinemia in Group 1 was higher than that in Group 3 (all P < 0.016). For related treatment, the usage rate of vasoactive substances and mechanical ventilation in Group 1 was higher than that of Group 2 and Group 3 (all P < 0.016). By Lasso and Logistic regression analysis, we found that GA (OR: 0.274, 95%CI: 0.078–0.796), sepsis (OR: 7.955, 95%CI: 1.424–65.21), coagulopathy (OR: 19.51, 95%CI: 3.393–179.1), CHD (OR: 6.99, 95%CI: 1.418–54.83) and diseased bowel segment (OR: 2.804, 95%CI: 1.301–7.316) were the independent factors for poor prognosis (all P < 0.05).ConclusionsThe clinical features of NEC-IP patients differ based on GA, particularly in terms of CHD type, postnatal day at the time of surgery, utilization of vasoactive substances, and prognosis. Furthermore, GA, sepsis, coagulopathy, CHD, and diseased bowel segment are independent factors for poor prognosis of patients with NEC-IP.